Historia Geográfica, Natural y Civil del Reino de Chile 1782 of the Jesuit Expelled Felipe Gómez de Vidaurre: A Work Unjustly Devalued by Chilean Historiography [Historia Geográfica, Natural y Civil del Reino de Chile 1782 del Jesuita Expulso Felipe Gómez de Vidaurre: Una Obra Injustamente Desvalorizada por la Historiografía Chilena] - Figueroa-Zuniga, M (Consejo Superior de Investigaciones Cientificas, Instituto de Economia y Geografia Aplicadas, 2017)
This paper will attempt to present the Historia geográfica, natural y civil del Reino de Chile by the Chilean Jesuit expelled Felipe Gómez de Vidaurre, that despite being forgotten by the Chilean historiography it contains interesting descriptions of the inhabitants of Chile in the late eighteenth century. It also offers some proposals to improve aspects of Chilean society, which makes it a valuable text for understanding the period preceding the independence of Chile. © 2017 CSIC.